2016
DOI: 10.1590/s0102-053620160418
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade da cebola fertirrigada sob diferentes doses de nitrogênio e densidades populacionais

Abstract: Onion productivity in fertigated system under different nitrogen levels and population densitiesOn onion, several studies have confirmed that the population density and nitrogen fertilization should be considered to combine quality and productivity. The experiment aimed to evaluate the effect of nitrogen by fertigation under different population densities on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
1
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 15 publications
4
7
1
13
Order By: Relevance
“…These results are in agreement with those reported by several authors who found increments in the production of bulbs in the Classes 3 and 4, due to the N fertilization in onion, with N doses ranging from 126 to 168 kg ha -1 for Class 3 (Cecílio Filho et al, 2010;Menezes Júnior & Kurtz, 2016;Resende et al, 2016).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with those reported by several authors who found increments in the production of bulbs in the Classes 3 and 4, due to the N fertilization in onion, with N doses ranging from 126 to 168 kg ha -1 for Class 3 (Cecílio Filho et al, 2010;Menezes Júnior & Kurtz, 2016;Resende et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…Leaf N concentration increased linearly, as a function of the N doses, with an estimated maximum of 28.37 g kg -1 ( Figure 1A). This result corroborates those obtained by Menezes Júnior & Kurtz (2016).…”
Section: Resultssupporting
confidence: 93%
“…Argissolo e Neossolo, respectivamente (Figura 1D). Aumento da produtividade de bulbos de classes com maior diâmetro com o incremento de doses de N e a redução na produtividade de bulbos de menor diâmetro tem sido observado (CECÍLIO FILHO et al, 2010;KURTZ et al, 2012;COSTA, 2014aCOSTA, e 2014bRODRIGUES et al, 2015;MENEZES JÚNIOR;KURTZ, 2016;GONÇALVES et al, 2019).…”
Section: Methodsunclassified
“…No campo, a fertilização com N aumenta a produção de cebola, entretanto a produção máxima de bulbos comercializáveis é variável com a cultivar/híbrido, época de cultivo, época de aplicação de N e tipo de solo (CECÍLIO FILHO et al, 2010;KURTZ et al, 2012;VILLAS BOAS et al, 2014;MENEZES JÚNIOR;KURTZ, 2016). Portanto, o manejo adequado do nitrogênio no programa de adubação é necessário, com vista no aumento do potencial produtivo da cultura.…”
Section: Introductionunclassified
“…Estudos relacionados à densidade ideal de cultivo para os cultivares locais têm sido desenvolvidos na Epagri -Estação Experimental de Ituporanga com o objetivo de verificar a possibilidade de maior adensamento das lavouras. Nestes, a população máxima testada para os cultivares foi de 600 mil plantas ha -1 , com respostas de severidade do míldio e produtividade dependentes das condições climáticas e sistema de produção utilizado (15,18,19,22).…”
unclassified